2021
DOI: 10.1111/gcb.15542
|View full text |Cite
|
Sign up to set email alerts
|

Optimal temperature of vegetation productivity and its linkage with climate and elevation on the Tibetan Plateau

Abstract: Vegetation productivity first increases and then decreases with temperature; and temperature corresponding to the maximum productivity is called optimal temperature (Topt). In this study, we used satellite derived near‐infrared reflectance of vegetation (NIRv) data to map Topt of vegetation productivity at the spatial resolution of 0.1° on the Tibetan Plateau (TP), one of most sensitive regions in the climate system. The average Topt of non‐forest vegetation on the TP is about 14.7°C, significantly lower than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(24 citation statements)
references
References 65 publications
1
23
0
Order By: Relevance
“…Vegetation productivity firstly increases and then decreases with temperature rises (the temperature corresponding to the maximum productivity is called optimal temperature, T opt ). Chen et al (2021) found that a remarkable geographical heterogeneity in T opt was observed over the QTP 30 . Higher T opt values generally appeared in the north-eastern parts, while the south-western QTP had relatively lower T opt (< 10 °C), and the average T opt of non-forest vegetation on the QTP was ~ 14.7 °C.…”
Section: Discussionmentioning
confidence: 99%
“…Vegetation productivity firstly increases and then decreases with temperature rises (the temperature corresponding to the maximum productivity is called optimal temperature, T opt ). Chen et al (2021) found that a remarkable geographical heterogeneity in T opt was observed over the QTP 30 . Higher T opt values generally appeared in the north-eastern parts, while the south-western QTP had relatively lower T opt (< 10 °C), and the average T opt of non-forest vegetation on the QTP was ~ 14.7 °C.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, many research studies have focused on the response of vegetation phenology to specific climate factors, including temperature, precipitation, and shortwave radiation. The results indicated that interaction between temperature, shortwave radiation, and water has caused various impacts on vegetation activities in different regions [16][17][18]. For example, the SOS arrived 2.5 days earlier, and the EOS was delayed by 1 day for every 1 • C increase in the temperature across 19 European countries [19].…”
Section: Introductionmentioning
confidence: 99%
“…For temperate ecosystems, increasing temperature in spring months seemed to enhance GPP more than to stimulate SIF emission, leading to an increasing GPP/SIF ratio as temperature continues to increase from spring to summer (Figures 5a, 7). In summer months, temperature increase has little impact on both GPP and SIF, perhaps because temperature is already at or near the optimum for photosynthesis (Chen, Huang, et al, 2021; Huang et al, 2019). Thus, the correlation between summer temperature and GPP/SIF is close to zero or even negative.…”
Section: Discussionmentioning
confidence: 99%